Perbandingan Aturan Hukum Iklan yang Menyesatkan di Negara Aanggota Association of Southeast Asian Nations - Nurzakiah, Nurzakiah; Yuliati, Yuliati; Sulistio, Faizin (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze consumer protection and compare legal regulations on misleading advertising in member countries of the Association of Southeast Asian Nations. This study used a normative juridical method with a legislative and conceptual approach. The results of the study show that consumer protection in ASEAN member countries is regulated in the ASEAN High-Level Principles, which consist of eight principles, namely enforcement of consumer protection laws, development of consumer skills in choosing products, guarantee of protection from dangerous products, provision of compensation mechanisms for consumers, education on environmental sustainability, provision of advocacy, cross sector cooperation, and consumer protection in e-commerce. ASEAN member countries as a whole have legal regulations related to misleading advertising, but not all countries describe in detail the criteria for advertising that can be categorized as misleading.